Microscopic research of shoots of the Salix cinerea L. of Ukrainian flora - N. V. Borodina; V. M. Kovalov; O. M. Koshovyi; O. V. Hamulia (Zaporozhye State Medical University, 2019)
Representatives of the Salicaceae family are valuable sources of medicinal plant material that has been used in traditional medicine in many countries around the world.. In European countries, some willow species are official plants. It is the bark of willow in many countries called natural aspirin. The decoction of the willow bark is used as an antimalarial, antipyretic, wound healing, antiseptic, hemostatic, astringent and anti-inflammatory agent. Plants of the genus Salix L. have a variety of component composition and contain a complex of biologically active compounds: primarily polyphenolic compounds, phenol glycosides, salicylates, flavonoids, hydroxycoric acids, essential oils, vitamins, carotenoids, polysaccharides. The bark of young branches of different willow species, including Salix purpurea L., Salix fragilis L., Salix daphnoides Vill., have been included in the edition of the European Pharmacopoeia and since 2014 to the State Pharmacopoeia of Ukraine. Expanding the raw material base of medicinal plant raw materials is an urgent problem that can be solved through the introduction into the pharmaceutical practice of systematically close autochthonous and introduced willow species widespread inUkraine. The purpose of this work is the determination of microscopic diagnostic features of the willow goat (Salix cinerea L.) shoots of Ukrainian flora for the plant material identification. Materials and methods. The object of the study was dry shoots of Salix cinerea L. Vegetable raw materials were collected in May-August 2016-2018 in Kharkiv, Zakarpattia and Kyiv region of Ukraine. The study of the anatomical structure of goat willow shoots was performed using the methods of light and electron microscopy. The ultrastructure of the epidermal leaf tissue surface was further studied using scanning microscopy techniques. Results. An in-depth study of the anatomical structure of the shoots of Salix cinerea L. has been carried out and the main diagnostic macro- and microscopic features of perspective medicinal raw materials have been established. Conclusions. The obtained results significantly expand information on the anatomical structure of shoots of Salix cinerea L. flora of Ukraine and could be used in the standardization of raw materials of species of the family Willow.